Animal husbandary practices of smallholder organic farmers in Uganda: Challenges and future prospects - Nalubwama, Sylvia; Kiggundu, Muhammad; Vaarst, Mette (Building Organic Bridges, 2014)
Organic agriculture development in Uganda has been mainly in crop production. Currently certified organic livestock production is non-existent. However, some of the existing animal husbandry practices of smallholder organic farmers are similar to those recommended in organic animal husbandry. A survey to understand these practices and challenges was conducted among ninety certified organic pineapple farmers in two districts using a semi-structured questionnaire. Results indicated that organic farmers kept a diversity of livestock species. Most organic farm (81%) had cattle. Other species owned were goats, pigs and chicken. Farmers mainly kept indigenous livestock breeds and majority (90%) used natural mating as a form of animal breeding. Farmers in Luwero district kept a significantly higher (P< 0.001) number of cattle (mean 2.3) than in Kayunga district (mean 1.6). Sixty four percent of farmers had no housing for their livestock. Natural pastures and crop residues formed bulk of feed for ruminants and pigs. Tethering was the commonest form of management system in ruminants (90%). Pigs (60%) and chicken (95%) were under free range system. There was a significant relationship (P= 0.047) between breed of cattle and grazing system. Major challenges of livestock production were inadequate feeds, pests and diseases. Selection of tolerant breeds and use of herbal concoctions were the adopted coping strategies. Majority of farmers (100%) resorted to use of synthetic chemical drugs in case of failure of these strategies. The future development of organic animal husbandry among smallholder organic farmers lies in developing sustainable research based technologies/ solutions to tackle existing and future challenges, investing in infrastructural development as well as improving farmer’s knowledge.
Keywords: Animal husbandry; Practices; Organic; Smallholder; Uganda